The Effectiveness of the Nurse Care Coordinator Role on Patient-Reported and Health Service Outcomes: A Systematic Review. Issue 3 (September 2019) - Conway, Aaron; O'Donnell, Chris; Yates, Patsy
This systematic review examined the effectiveness of nurse care coordinator (CC) roles on patient-reported and health service outcomes. Multiple electronic databases (Medline, CINAHL, and EMBASE) were searched and the Cochrane Risk of Bias Assessment Tool was applied by two independent reviewers. The Grades of Recommendation, Assessment, Development, and Evaluation system was used to assess the quality of evidence. A total of 45 articles (reporting on 36 studies) were included. The majority of studies ( n = 28, 78%) were conducted in the United States and published after 2009 ( n = 24, 67%). Thirteen studies (36%) used a randomized controlled trial design. A total of 17 studies evaluated patient-reported outcomes and 29 studies reported health service outcomes. The individual components of nurse CC roles that were evaluated ranged considerably. The impact of nurse care coordination on patient-reported and health service outcomes was inconsistent. There was an indication from higher quality studies that nurse care coordination roles were more likely to result in improved patient and health service outcomes where they involved frequent, in-person interactions, had ongoing follow-up with monitoring of disease status, and involved transition care and the application of behavior change principles.